(untitled) (Bangladesh Journal of Genetics and Biotechnology, 2008)
No abstract available. Key words: Callosobruchus ; reproductive potential; gamma radiation; probit mortality and sterility responses Bangladesh j. genet. biotechnol. 6 (1&2): 23-28, 2005 (June & December)